A First Comparative Study of Oesophageal and Voice Prosthesis Speech Production. (2nd June 2009) - Carello Carello, Massimiliana Massimiliana; Magnano Magnano, Mauro Mauro
Abstract : The purpose of this work is to evaluate and to compare the acoustic properties of oesophageal voice and voice prosthesis speech production. A group of 14 Italian laryngectomized patients were considered: 7 with oesophageal voice and 7 with tracheoesophageal voice (with phonatory valve). For each patient the spectrogram obtained with the phonation of vowel /a/ (frequency intensity, jitter, shimmer, noise to harmonic ratio) and the maximum phonation time were recorded and analyzed. For the patients with the valve, the tracheostoma pressure, at the time of phonation, was measured in order to obtain important information about the "in vivo" pressure necessary to open the phonatory valve to enable speech.